Proteomic analysis of integrin alphaIIbbeta3 outside-in signaling reveals Src-kinase-independent phosphorylation of Dok-1 and Dok-3 leading to SHIP-1 interactions. - Senis, Y; Antrobus, R; Severin, S; Parguiña, A; Rosa, I; Zitzmann, N; Watson, S; García, A (Wiley, 2009)
BACKGROUND AND OBJECTIVES: Outside-in integrin alphaIIbbeta3 signaling involves a series of tyrosine kinase reactions that culminate in platelet spreading on fibrinogen. The aim of this study was to identify novel tyrosine phosphorylated signaling proteins downstream of alphaIIbbeta3, and explore their role in platelet signaling. METHODS AND RESULTS: Utilizing proteomics to search for novel platelet proteins that contribute to outside-in signaling by the integrin alphaIIbbeta3, we identified 27 proteins, 17 of which were not previously shown to be part of a tyrosine phosphorylation-based signaling complex downstream of alphaIIbbeta3. The proteins identified include the novel immunoreceptors G6f and G6b-B, and two members of the Dok family of adapters, Dok-1 and Dok-3, which underwent increased tyrosine phosphorylation following platelet spreading on fibrinogen. Dok-3 was also inducibly phosphorylated in response to the GPVI-specific agonist collagen-related peptide (CRP) and the PAR-1 and -4 agonist thrombin, independently of the integrin alphaIIbbeta3. Tyrosine phosphorylation of Dok-1 and Dok-3 was primarily Src kinase-independent downstream of the integrin, whereas it was Src kinase-dependent downstream of GPVI. Moreover, both proteins inducibly interacted with Grb-2 and SHIP-1 in fibrinogen-spread platelets. CONCLUSIONS: This study provides new insights into the molecular mechanism regulating alphaIIbbeta3-mediated platelet spreading on fibrinogen. The novel platelet adapter Dok-3 and the structurally related Dok-1 are tyrosine phosphorylated in an Src kinase-independent manner downstream of alphaIIbbeta3 in human platelets, leading to an interaction with Grb2 and SHIP-1.